2017
DOI: 10.1016/j.jclepro.2017.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of waste concrete through CO2 mineral carbonation: Optimizing parameters and improving reactivity using concrete separation

Abstract: The use of CO 2 mineral carbonation represents an attractive approach to recycling waste concrete. In this study, the effect of gas pressure, Liquid/Solid (L/S) ratio (w/w), Gas/Liquid (G/L) ratio (v/v) and reaction time for CO 2 sequestration were investigated. While carbonation of such matrix is already described, this study opens new insights in concrete carbonation. To increase the reactivity potential of concrete, the fine fraction (<500 μm), which contains mostly cement paste, was separated from the iner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…[59][60][61][62][63] including the binders based on special, low hydraulically active clinkers 41,64,65 . Lately, some authors suggested that the recycled concrete fines can be valorized by carbonation for the use in the concrete production 66,67 . Studies on the carbonation of the hydrated cement pastes revealed that carbonation is occurring at mild conditions, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…[59][60][61][62][63] including the binders based on special, low hydraulically active clinkers 41,64,65 . Lately, some authors suggested that the recycled concrete fines can be valorized by carbonation for the use in the concrete production 66,67 . Studies on the carbonation of the hydrated cement pastes revealed that carbonation is occurring at mild conditions, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The dissolution of Ca(OH)2 in concrete by the solubility product constant (Ksp of Ca(OH)2 = 5.5 × 10 −6 ) results in several alkaline solutions (approximately pH 12.6) and Ca saturation in solution (approximately 800 mg/L) according to Equation (3). In the field plant, the solution pH and Ca concentration conditions could fluctuate on a daily basis.…”
Section: Co2(g) → Co2(aq)mentioning
confidence: 99%
“…The high concentration of dissolved Ca 2+ , Na + , K + and OH − in the sludge solution increased the EC to approximately 8.9 dS/m [26,27]. Quartz (SiO 2 ), calcite (CaCO 3 ) and the feldspar mineral albite (NaAlSi 3 O 8 ) were identified by XRD in dried sludge particles (Figure 4a) [3]. Portlandite (Ca(OH) 2 ), present in the original concrete (Figure 4b), was not observed in the concrete sludge XRD spectrum, possibly due to dissolution during the wet-based crushing/screening process.…”
Section: Physicochemical Characteristics Of the Samplementioning
confidence: 99%
See 2 more Smart Citations